The influence of Marketing Mix Less Salt Seasoning on perceived value and purchase intention - Priyanka Prima Dewi; Atik Aprianingsih (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
Spices and seasoning market showed good growth with CAGR 6% from 2021-2026 driven by the increment of customer demand and home cooking habit. The increasing of healthy lifestyle and Indonesia government policy in supporting healthy food product are become opportunity for seasoning industry to launch healthy value-added seasoning. This research aims to know marketing mix that influences perceived value and drive purchase intention of less salt flavor seasoning. The research conducted in Jakarta area with 320 respondents from gender male & female, age range 20-50 years old and various occupations. The research also collected data for respondents’ cooking, eating habit and their response on research hypothesis indicators. This research used PLS-SEM analysis and showed that product, price and promotion significantly influence perceived value and purchase intention. However, place does not significantly influence perceived value and purchase intention. The research result will be beneficial for seasoning industry in developing marketing strategy for healthy value-added seasoning.